The Effect of Innovative Technology Benefits and E-Commerce Using Motivations on Customer Experience and Customer Information - Zahra Bigdelou; Alireza Rousta; Farzad Asayesh (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: This study aims to determine the effect of technology benefits and motivations for using e-commerce on customer experience and consumer information with the mediating role of pleasure and timely use.Methodology: The present study is applied research regarding the purpose and a descriptive survey regarding the implementation method. The statistical population of the study was all customers of Digi Kala Co. Due to the uncertainty of these customers, based on Cochran's formula at a level of 5% error, 384 people were selected as a sample. The sampling method was random sampling.Findings: The results showed that the usefulness of technology positively affects the user's sense of satisfaction. Technology has a positive effect on the timely use of the user. Motives for using e-commerce positively influence the user's sense of satisfaction. Motives for using e-commerce have a positive effect on the timely use of the user. The user's sense of satisfaction positively affects the customer experience. The user's sense of satisfaction has a positive effect on customer information. Timely use of the user has a positive effect on the customer experience. Timely use of the user has a positive effect on customer information. The usefulness of technology has a positive effect on the customer experience by mediating the user's sense of satisfaction. The usefulness of technology has a positive effect on the customer experience by mediating the timely use of the user. The usefulness of technology has a positive effect on customer information by mediating the user's sense of satisfaction. The usefulness of technology has a positive effect on customer information by mediating the timely use of the user. Motives for using e-commerce positively affect the customer experience by mediating the user's sense of satisfaction. Motives for using e-commerce have a positive effect on the customer experience by mediating the timely use of the user. Motives for using e-commerce positively affect customer information by mediating the user's sense of satisfaction. Motives for using e-commerce have a positive effect on customer information by mediating the timely use of the user.Originality/Value: This study investigates the relationship between the benefits of technology innovation and e-commerce using motivations with customer information and consumer experience with the mediating role of pleasure and timely use.